2019
DOI: 10.1002/path.5242
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapeutic potential of group 2 innate lymphoid cells in acute kidney injury

Abstract: Acute kidney injury (AKI) remains a global challenge and, despite the availability of dialysis and transplantation, can be fatal. Those that survive an AKI are at increased risk of developing chronic kidney disease and end stage renal failure. Understanding the fundamental mechanisms underpinning the pathophysiology of AKI is critical for developing novel strategies for diagnosis and treatment. A growing body of evidence indicates that amplifying type 2 immunity may have therapeutic potential in kidney injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 91 publications
(156 reference statements)
1
15
0
Order By: Relevance
“…The M2 phenotype can be induced ex vivo or in vivo via IL‐10 and transforming growth factor (TGF)‐β stimulation for treating kidney diseases . The type 2 innate lymphoid cells (ILC2s), which are a recently described innate immune cell population that can be activated by IL‐33 or IL‐25, also contribute to M2 polarization of macrophages through secretion of various type 2 cytokines, such as IL‐4 and IL‐13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M2 phenotype can be induced ex vivo or in vivo via IL‐10 and transforming growth factor (TGF)‐β stimulation for treating kidney diseases . The type 2 innate lymphoid cells (ILC2s), which are a recently described innate immune cell population that can be activated by IL‐33 or IL‐25, also contribute to M2 polarization of macrophages through secretion of various type 2 cytokines, such as IL‐4 and IL‐13 …”
Section: Introductionmentioning
confidence: 99%
“…13 The type 2 innate lymphoid cells (ILC2s), which are a recently described innate immune cell population that can be activated by IL-33 or IL-25, also contribute to M2 polarization of macrophages through secretion of various type 2 cytokines, such as IL-4 and IL-13. [14][15][16] Recent studies have demonstrated that macrophages can be potentially used in cell therapies to induce immune tolerance to transplantation and to promote wound healing. 17,18 Cao Q et al 13,19 polarized the splenic macrophages to the M2 phenotype, which effectively reduced renal injury, by adoptive transfer of M2 macrophages to experimental models of adriamycin-induced kidney disease.…”
mentioning
confidence: 99%
“…This property likely contributes to the important roles of ILCs not only in immune responses against pathogens and sterile inflammation but also in maintaining tissue hemostasis. Nonetheless, differential development and activation of ILCs in a context-and/or disease-specific manner may contribute to inflammatory responses and/or outcome of treatment modalities [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, immunomodulatory strategies that are aimed at shifting the balance from a pro-inflammatory, tissue destructive immune response in the kidney to an anti-inflammatory, pro-regenerative response are promising candidates for the development of novel therapies for kidney diseases. In this context, several recent studies identified kidney-residing Innate lymphoid cells (ILCs) as potential therapeutic targets in the attempt to promote tissue regeneration in AKI and/or slow progression of CKD (8).…”
Section: Introductionmentioning
confidence: 99%